Trade-offs between carbon conservation and profitability in crop cultivation: unlocking potential through diversifying crop allocations regionally - Eveliina Kiiaki; Kari Hyytiäinen (Agricultural and Food Science)
Adjusting crop rotation is a key agricultural strategy to boost variable profit, enhance soil fertility, adapt to climate change, and mitigate farming risks. The aim of this paper is to assess the opportunities for simultaneously enhancing carbon balance and variable profit of crop cultivation through altering the allocation of crop use in a regional scale. Using a numerical optimization model for mineral soils in southern Finland, results show that careful diversifying of crop cultivation can enhance both carbon balance and profit compared to the current allocation. Including the lifecycle carbon footprint of nitrogen fertilizers further increases potential gains. Variable profit can rise by 75–207 € ha-1 year-1, while carbon balance improves by 70–336 kg C ha-1 year-1, depending on the weighting of economic and climate outcomes. Changes can be made without significantly increasing fixed costs of cultivation. Optimal strategies include reducing spring crops and fodder grass while increasing nitrogen-fixing grasses and high-profit crops like clover grass, green manure, potato, and sugar beet. Sensitivity analysis highlighted the importance of higher yields for enhanced outcomes, emphasizing the need to enhance forage grass, clover grass, and green manure yields for carbon balance and forage grass, potato, sugar beet, and spring crop yields for increased variable profit. Investments in infrastructure, marketing, and innovative food products are essential to promote local crop diversity and incentivize farmers to utilize and test new crops on a farm.